Physical stability and biological activity of biofilms under turbulent flow and low substrate concentration - Melo, L. F. (1999)
The paper focuses on biofilms subject to turbulent flow and high liquid velocity (of the order of 1 m s ˉ¹) which can be found in heat exchangers, water distribution systems and in some wastewater reactors. An overall model describing biofilm development is presented, which includes the effects of biomass detachment due to the hydrodynamic forces. A methodology for estimating substrate consumption from data obtained through continuous monitoring of biofilm growth is presented. Results show that the physical stability of the biofilm increases with the liquid velocity, while the rate of substrate consumption decreases.